2014
DOI: 10.1097/pas.0000000000000262
|View full text |Cite
|
Sign up to set email alerts
|

“Somatic-type” Malignancies Arising From Testicular Germ Cell Tumors

Abstract: Somatic-type malignancies (SMs) in patients with testicular germ cell tumors (GCT) are rare and mostly attributed to "transformation" of teratoma, although yolk sac tumor (YST) origin has also been proposed. We studied 124 cases of "SM" of testicular GCT origin from 106 patients to evaluate their morphology, immunohistochemical features (especially the utility of SALL4), and relationship to YST. Primitive neuroectodermal and nephroblastomatous tumors were excluded because of prior studies. Patients ranged in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 50 publications
0
47
1
Order By: Relevance
“…In a study, the mean age for TGCT patients was 33 years (14). Assi et al (12) reported that the mean age for testicular tumors was 32 years.…”
Section: Discussionmentioning
confidence: 99%
“…In a study, the mean age for TGCT patients was 33 years (14). Assi et al (12) reported that the mean age for testicular tumors was 32 years.…”
Section: Discussionmentioning
confidence: 99%
“…Somatic-type malignancy: While the development of somatic-type malignancy is not a phenomenon exclusively found in post-chemotherapy specimens, it is more commonly seen in this setting [135]. The most common histologies are peripheral neuroectodermal tumors, rhabdomyosarcoma and other sarcomas, and adenocarcinomas; however, a wide spectrum of somatic histologic types has been described.…”
Section: Pathologic Findings In Postchemotherapy Rplnd Specimensmentioning
confidence: 98%
“…The term sarcomatoid YST has been used to describe tumors with spindled cellular stroma that retains cytokeratin reactivity. A recent study [135] has proposed that some somatic sarcomatoid malignancies may actually represent sarcomatoid YST. Hepatoid YST consists of cells with abundant eosinophilic cytoplasm, large central nucleus, and prominent nucleolus arranged in nests, cords, or trabeculae.…”
Section: Microscopymentioning
confidence: 99%
See 2 more Smart Citations